Unearthing Perspectives from Aristotle's Nicomachean Ethics and Islamic Adl: Discourse of Settler Colonialism in South Africa - Saemah Shamim; Muhammad Muhammad Nasir (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2024)
This study explores the enduring impacts of settler colonialism on contemporary South Africa, examining how it continues to shape issues of identity, citizenship, belonging, and social injustices. Moving beyond problem-solving, the research delves into ancient philosophical and Islamic ethical concepts of a just society. Two frameworks are compared: Aristotle's theories of justice, particularly from Books III and V of his Nicomachean Ethics (which cover the same material as Book IV of Eudemian Ethics), and the Islamic concept of Adl. By analyzing these frameworks and applying critical methods to South African discourse, including keynote speeches, the study aims to develop a more robust understanding of justice in the context of settler colonialism's lasting inequalities. This paper seeks to articulate and expand the conceptual understanding of these two frameworks, providing a richer philosophical and normative picture to inform current discussions on the legacy of settler colonialism. The study employs a qualitative approach, using document analysis, comparative analysis, and critical methods to analyze data. These methods are used to discuss the presented theories of justice. Additionally, in the South African setting, keynote speeches were analyzed as primary data.